Clinical role of frequency‐doubled double‐pulse neodymium YAG laser lithotripsy for removal of difficult biliary stones in laparoscopic common bile duct exploration. Issue 9 (23rd August 2019) - Yang, Tingsong; Ma, Zhilong; Xu, Bin; Sun, Wei; Meng, Hongbo; Liu, Dalu; Zhou, Bo; Song, Zhenshun
Abstract : Background: The optimal methods for patients with difficult biliary stones remain under debate. The aim of this study was to evaluate the role of frequency‐doubled double‐pulse neodymium YAG (FREDDY) laser lithotripsy for removing difficult biliary stones during laparoscopic common bile duct exploration (LCBDE). Methods: Between March 2013 and January 2015, 42 consecutive patients with difficult biliary stones who underwent LCBDE with FREDDY laser lithotripsy were included in this study. The clinical data of all patients were retrospectively collected and analysed. Results: Bile ducts were completely cleared in all patients. The complications related to laser lithotripsy were not noted. A total of 38 patients (90.5%) underwent primary closure of common bile duct, and T‐tube drainage was applied to four patients (9.5%). No bile duct injury, bleeding and perforation were observed. There were no post‐operative surgery‐related deaths. Bile leakage occurred in four patients (9.5%) with primary closure procedure, and all of them were managed successfully with conservative therapy. The median follow‐up period was 42.8 months, with no evidence of bile duct stricture and stone recurrence in all patients. Conclusions: The LCBDE combined with FREDDY laser lithotripsy appear to be effective and safe for the treatment of difficult biliary stones. Abstract : The optimal methods for patients with difficult biliary stones remain under debate. Laparoscopic common bile duct exploration combined with frequency‐doubled double‐pulse neodymium YAG laser lithotripsy appear to be effective and safe for the treatment of difficult biliary stones.